STAFF SUPERVISION AND DISCIPLINE IN A SCHOOL AS AN ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
The present paper discusses staff supervision and discipline in a school context. As we know, inorder to maintain an efficient and effective work environment, employees are often required toaddress inappropriate behaviour and / or performance through corrective and / or disciplinaryaction. Supervision is a process by which a trained professional provides regular support,instruction and feedback to peer supporters. The process is designed to ensure the emotionalwell being of both the peer supporters and the clients accessing the program. The benefits ofsupervision include enhanced accountability, increased feeling of support, development ofprofessional skills and improved efficiency. Supervision is also associated with decreasedfeelings of isolation and role ambiguity. The increased morale generated by supervisionultimately results in lower levels of volunteer burnouts. The supervisor being the manager in adirect contact with the operatives, has got multifarious functions to perform. The objectivebehind performance of these functions is to bring stability and soundness in the organisationwhich can be secured through increase in profits and better results which is an end result ofhigher productivity. Therefore, a supervisor needs to make sure that all his / her members ofstaff are well disciplined and focused at their core business all the time.